Nicotine modulates human brain plasticity via calcium‐dependent mechanisms. (17th October 2018) - Grundey, Jessica; Barlay, Jerick; Batsikadze, Giorgi; Kuo, Min‐Fang; Paulus, Walter; Nitsche, Michael
Abstract : Key points: Nicotine (NIC) modulates cognition and memory function by targeting the nicotinic ACh receptor and releasing different transmitter systems postsynaptically. With both NIC‐generated mechanisms, calcium influx and calcium permeability can be regulated, which is a key requirement for the induction of long‐term potentiation, comprising the physiological basis of learning and memory function. We attempt to unmask the underlying mechanism of nicotinic effects on anodal transcranial direct current stimulation (tDCS)‐induced long‐term potentiation‐like plasticity based on the hypothesis of calcium‐dependency. Abolished tDCS‐induced neuroplasticity as a result of NIC administration is reversed by calcium channel blockade with flunarizine in a dose‐dependent manner. The results of the present study suggest that there is a dose determination of NIC/NIC agonists in therapeutical settings when treating cognitive dysfunction, which partially explains the heterogeneous results on cognition observed in subjects in different experimental settings. Abstract: Nicotine (NIC) modulates neuroplasticity and improves cognitive performance in animals and humans mainly by increased calcium permeability and modulation of diverse transmitter systems. NIC administration impairs calcium‐dependent plasticity induced by non‐invasive brain stimulation with transcranial direct current stimulation (tDCS) in non‐smoking participants probably as a result of intracellular calcium overflow. To test this hypothesis, we analysed the effect of calcium channel blockade with flunarizine (FLU) on anodal tDCS‐induced cortical excitability changes in healthy non‐smokers under NIC. We applied anodal tDCS combined with NIC patch and FLU at three different doses (2.5, 5 and 10 mg) or with placebo medication. NIC abolished anodal tDCS‐induced neuroplasticity. Under medium dosage (but not under low and high dosage) of FLU combined with NIC, plasticity was re‐established. For FLU alone, the lowest dosage weakened long‐term potentiation (LTP)‐like plasticity, whereas the highest dosage again abolished tDCS‐induced plasticity. The medium dosage turned LTP‐like plasticity in long‐term depression‐like plasticity. The results of the present study suggest a key role of calcium influx and calcium levels in nicotinic effects on LTP‐like plasticity in humans. This knowledge might be relevant for the development of new therapeutic strategies in cognitive dysfunction. Key points: Nicotine (NIC) modulates cognition and memory function by targeting the nicotinic ACh receptor and releasing different transmitter systems postsynaptically. With both NIC‐generated mechanisms, calcium influx and calcium permeability can be regulated, which is a key requirement for the induction of long‐term potentiation, comprising the physiological basis of learning and memory function. We attempt to unmask the underlying mechanism of nicotinic effects on anodal transcranial direct current stimulation (tDCS)‐induced long‐term potentiation‐like plasticity based on the hypothesis of calcium‐dependency. Abolished tDCS‐induced neuroplasticity as a result of NIC administration is reversed by calcium channel blockade with flunarizine in a dose‐dependent manner. The results of the present study suggest that there is a dose determination of NIC/NIC agonists in therapeutical settings when treating cognitive dysfunction, which partially explains the heterogeneous results on cognition observed in subjects in different experimental settings.